2018
DOI: 10.4172/2161-0509.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Malnutrition among Pregnant Women and Associated Factors in Central Refit Valley of Ethiopia, 2016

Abstract: Background: Pregnancy strongly depends on the health and nutritional status of women. High proportion of pregnant women affected with poor nutrition which leads them to unhealthy and distress condition. Nutritional problem alongside difficulty of ecological exacerbates public health problem. Determining the extent of problems and predicting marked health indicator require extensive studies to improve pregnant women health to reduce maternal in lowland distracts.Objective: This study aimed to determine the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 19 publications
(25 reference statements)
4
37
6
1
Order By: Relevance
“…The variation might be due to distinctions in MUAC cut of value, and the socio-culture distinctions between Ethiopia and the other counties. The present study nding was lower than those of studies done in other areas of Ethiopia reported 72%, 34%, 31.8%, 31.4%, 30.3% and 28.6% (26,27,(37)(38)(39)(40). In the current study prevalence of maternal undernutrition shows a little decrement in compared to previous studies done in the study area.…”
Section: Discussioncontrasting
confidence: 85%
“…The variation might be due to distinctions in MUAC cut of value, and the socio-culture distinctions between Ethiopia and the other counties. The present study nding was lower than those of studies done in other areas of Ethiopia reported 72%, 34%, 31.8%, 31.4%, 30.3% and 28.6% (26,27,(37)(38)(39)(40). In the current study prevalence of maternal undernutrition shows a little decrement in compared to previous studies done in the study area.…”
Section: Discussioncontrasting
confidence: 85%
“…We found that a significant proportion of pregnant women had low MUAC. In a study conducted in Ethiopia, a similar prevalence of low MUAC (31.8%) was reported among pregnant women (Mariyam & Dibaba, ), although this study applied a cutoff of 21 cm.…”
Section: Discussionmentioning
confidence: 58%
“…These articles were from six regional state and two cities of Ethiopia. Eight studies were done in Oromo regional state [25,26,28,30,31,33,46,47], six articles in Amhara region [32,[48][49][50][51][52], four articles from South Nation and Nationality of People (SNNP) [27,34,53,54], two articles in Tigray [29,55] and in Addis Ababa (AA) [56], Dire Dawa [57], Gambella [58] and Ethiopian Somalia [59] shared single articles for each.…”
Section: Explanation For Original Studiesmentioning
confidence: 99%
“…Moreover, this review found that iron supplementation during pregnancy was protective for malnutrition among pregnant women. Its protective effect was listed in two of the included articles [29,33]. Pregnant women who supplied with iron during pregnancy were 0.63 times risk of being malnutrition than their counterparts (OR = 0.63, 95% CI: 0.45, 0.88).…”
Section: Predictors Of Malnutrition Among Pregnant Women In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation